Carboxyl Methyltransferase Catalysed Formation of Mono‐ and Dimethyl Esters under Aqueous Conditions: Application in Cascade Biocatalysis. Issue 14 (16th February 2022) - Ward, Lucy C.; McCue, Hannah V.; Rigden, Daniel J.; Kershaw, Neil M.; Ashbrook, Chloe; Hatton, Harry; Goulding, Ellie; Johnson, James R.; Carnell, Andrew J.
Abstract: Carboxyl methyltransferase (CMT) enzymes catalyse the biomethylation of carboxylic acids under aqueous conditions and have potential for use in synthetic enzyme cascades. Herein we report that the enzyme FtpM from Aspergillus fumigatus can methylate a broad range of aromatic mono‐ and dicarboxylic acids in good to excellent conversions. The enzyme shows high regioselectivity on its natural substrate fumaryl‐l ‐tyrosine, trans, trans ‐muconic acid and a number of the dicarboxylic acids tested. Dicarboxylic acids are generally better substrates than monocarboxylic acids, although some substituents are able to compensate for the absence of a second acid group. For dicarboxylic acids, the second methylation shows strong pH dependency with an optimum at pH 5.5–6. Potential for application in industrial biotechnology was demonstrated in a cascade for the production of a bioplastics precursor (FDME) from bioderived 5‐hydroxymethylfurfural (HMF). Abstract : The carboxyl methyltransferase FtpM can catalyse methylation and dimethylation of a wide range of mono‐ and dicarboxylic acids, showing high regioselectivity for some diacids. The enzymatic methylation works under aqueous conditions and can therefore be integrated into enzyme cascades as demonstrated by the two‐step, one‐pot conversion of bioderived HMF to bioplastics precursor FDME.